Loneliness Pada Individu Lanjut Usia Berdasarkan Peran Religiusitas - Nisa Hermawati; Ila Nurlaila Hidayat (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
The purpose of this research is to find description about loneliness on elderly people who have religiosity. The research using description method with phenomenology. Phenomenology studies were chosen to identify the nature of experience and to understand the life experiences of the elderly people about loneliness. Subjects consisted of two elderly people who experience loss situation such as retiring from work with key positions as well as the death of a spouse. The results show the aspects of personality remain confident, in the aspect of social propriety can continue in harmony with the environment and not depressed or isolated, as they are still able to join the social environment. Religiosity factor plays an important role for both the subject and so they do not experience loneliness as is generally the elderly people who face a loss situation.